Whose Security Matters?. (15th August 2022) - Jamshidi, Maryam
Abstract : Claims to security are everywhere. They are used by states to justify invading other nations 1 and to derogate from international law obligations. 2 They are invoked by governments as reasons to exclude foreign nationals from their territory; 3 surveil their citizens; 4 and kill citizens and foreigners alike by remote control. 5 Some experts use security claims to underscore the seriousness of global threats, like COVID-19. 6 Security claims are also used by communities to defend their rights and well-being from those threatening them, including the state itself. 7 Still others criticize the use of security discourse—in at least some circumstances—describing it as undermining the rule of law. 8 Embedded within these claims is a view about whose security matters most—something that is also implicitly reflected in J. Benton Heath's four-part typology of security claims described in his recent article, "Making Sense of Security." 9 This essay explores the importance of whose security matters to Heath's framework. It does so by examining one political movement currently challenging the U.S. national security state. This movement is led by members of groups targeted and disadvantaged by U.S. national security policies—namely, Muslim, African, Middle Eastern, and South Asian communities. In that movement's recently released policy agenda, Abolishing the War on Terror & Building Communities of Care: A Grassroots Policy Agenda for the Biden-Harris Administration and 117th Congress ( Abolishing the War on Terror ), 10 its leaders call for abolishing the national security state and the War on Terror that it birthed. 11